Analysis of petroleum coke from low grade oily sludge of refinery. (18th June 2018) - Demirbas, Ayhan; Acar, Sukru; Horasan, Bilgehan Yabgu; Alalayah, Walid M.
ABSTRACT: Petroleum coke is often shortened as pet coke. Petroleum coke or pet coke is a product obtained from oil of all kinds during the oil refining process. Petroleum coke is a carbon-rich solid originating from petroleum refining and is obtained by cracking process. Petroleum coke is a byproduct of the coking unit, a residual fuel upgrader. The coke quality depends on the crude oil processed in refinery. The mixture of oil, solids and water deposited at the bottom of the storage deposit is known as waste oil sludge. Oil sludge is one of the solid wastes produced in petroleum refinery and it is a complex emulsion composed of various petroleum hydrocarbons, heavy metals, solid particles, and water. As a result of the refining process of crude oil, the contaminated sludge is biodegraded and converted into waste products that damage the environment and human health. In the coke processing, the assessment of oil sludge fraction is based on the principle of heating to high temperatures and the removal of light fractions from the breakdown. If the oil sludge initially contains low levels of sulfur and metal, the resulting petroleum coke is then calcined before use. The high quality needle type coke produced on convenient conditions in the coking unit.